Design and FEM Analysis of Laparoscopical Tool for Electrocoagulation Surgery - Vondrak, Jaroslav; Grepl, Jan; Penhaker, Marek; Hlavackova, Milada; Kovar, Petr; Kubicek, Jan (2019 IEEE 17th World Symposium on Applied Machine Intelligence and Informatics (SAMI), 2019)
This paper deals with the design and construction of the electrosurgery instrument for hysteroscopy, which would replace the current set of tools, shorten the time required to perform the procedure and make it easier, safer and more precise to use. In this paper, we have proposed a designing the mechanism of the new instrument and its own shape, dimensions, manufacturing the prototype, testing and measurement of the required parameters. The resulting device is primarily intended for the finite element method strength analysis of the proposed instrument.